Book Review of Learning to Learn Online - Xinyue Ren (Open Praxis, 2022)
Kwantlen Polytechnic University Learning Centres (2018). Learning to Learn Online. Kwantlen Polytechnic University. 100 pages. B.C. Open Textbook Collection (eBook). ISBN: 978-1-989864-10-4 (eBook). https://kpu.pressbooks.pub/learningtolearnonline/.